Ekstraksi dan Identifikasi Metabolit Sekunder Tanaman Obat sebagai Antimalaria di Kabupaten Keerom - Dehi, Rosita Irianti; Iriani, Fitriah Ardiawijianti; Damar, Alpha Christyananda (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Malaria remains a significant public health issue in Indonesia, particularly in endemic areas such as Keerom Regency, Papua. Efforts to control this disease face challenges due to Plasmodium resistance to synthetic drugs, highlighting the need for safer and more effective alternative treatments. This study aims to identify the secondary metabolite content of several local plants traditionally used as antimalarial remedies. An experimental laboratory study was conducted using phytochemical screening methods. The plants examined included turmeric rhizome (Curcuma longa), meniran leaves (Phyllanthus niruri), papaya leaves (Carica papaya), sambiloto (Andrographis paniculata), and brotowali (Tinospora crispa). Extraction was carried out using the maceration method with 96% ethanol as the solvent. The results showed that all samples contained secondary metabolites such as flavonoids, alkaloids, tannins, and saponins, which are known for their antiplasmodial activity. Extract yields ranged from 18% to 24%, with turmeric rhizome showing the highest yield. These findings suggest that local plants from Keerom Regency hold potential as raw materials for the development of herbal antimalarial drugs. This study serves as a preliminary step for further in vitro and in vivo bioactivity testing.